2020
DOI: 10.1111/ijcp.13651
|View full text |Cite
|
Sign up to set email alerts
|

Association between the variability of cerebral oxygen saturation during cardiopulmonary bypass and delayed postoperative neurocognitive recovery in cardiac valve surgical patients: A pilot study

Abstract: Aims of the study The association between regional cerebral oxygen saturation (rSO2) and postoperative cognitive decline is controversial. In this study, we investigated the association between the real variability of regional cerebral oxygen saturation during cardiopulmonary bypass (CPB) and postoperative delayed neurocognitive recovery in patients undergoing heart valve surgery. Methods used to conduct the study A total of 71 patients who underwent cardiac valve surgery were enrolled in this study. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…POD is an acute change in cognitive function and significantly increases the risk of POCD. 48,49 Though the duration of anaesthesia, CPB, hospital stay and ICU stay were not different across studies, [22][23][24][25][26]28,32,34,41 the studies failed to consider the potential interaction effects of all these factors associated with anaesthesia type and medications. Schoen et al 21 assessed the relationship between the interaction of anaesthesia, duration and desaturation and cognitive test results (Trail-Making, Abbreviated Mental, Stroop Test and Word List).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…POD is an acute change in cognitive function and significantly increases the risk of POCD. 48,49 Though the duration of anaesthesia, CPB, hospital stay and ICU stay were not different across studies, [22][23][24][25][26]28,32,34,41 the studies failed to consider the potential interaction effects of all these factors associated with anaesthesia type and medications. Schoen et al 21 assessed the relationship between the interaction of anaesthesia, duration and desaturation and cognitive test results (Trail-Making, Abbreviated Mental, Stroop Test and Word List).…”
Section: Discussionmentioning
confidence: 99%
“…In individuals less than 65 years, studies provide two types of findings: anaesthetics‐related adverse events associated with POCD 24,30,32,35–37,46 and intraoperative anaesthesia management (other than anaesthetics) 23,25,27,29,33,34,36,41 . It is found that intraoperative administration of ketamine 24 and dexmedetomidine 35 is associated with a decreased risk of POCD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations